Penyusunan Laporan Keuangan untuk Wajib Pajak UMKM Berbasis SAK EMKM Sebagai Dasar Pelaporan SPT Tahunan - Nurul Aisyah Rachmawati; Rizka Ramayanti; Muyassaroh Muyassaroh; Sri Opti (Jurnal Abdimas BSI: Jurnal Pengabdian Kepada Masyarakat, 2021)
As a form of fulfilling the Tri Dharma Perguruan Tinggi, Department of Accounting Universitas Trilogi does not only focus on teaching and research, but also on community service. In collaboration with Kantor Wilayah DJP Jakarta Selatan 1, Department of Accounting Universitas Trilogi conducted training in preparing financial reports based on SAK EMKM for UMKM Taxpayers in the KPP Pancoran Jakarta as the basis for reporting their Annual Tax Return. This activity was held on Tuesday, February 25th, 2020. The knowledge of UMKM Taxpayers in the KPP Pancoran Jakarta about financial and tax reporting is still very limited. This is what underlies the Community Service Team to conduct training activities in preparing financial and tax reports. The training consisted of three sessions: 1) giving material on preparing financial reports; 2) providing material about preparing tax reports; and 3) discussion and Q&A with the training participants. Because of the enthusiasm of the participants was very high, the training activities were followed by a mentoring session on the preparation of financial and tax reports held at Universitas Trilogi. Thus, participants get a better understanding and can report Annual Tax Return on time.